2018
DOI: 10.1080/1343943x.2018.1432981
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of plant density on growth and yield of new soybean genotypes grown under early planting condition in southwestern Japan

Abstract: Soybeans planted in early to mid-June (early) are less affected by rainfall during rainy season than those conventionally planted in early to mid-July in southwestern Japan. Also, narrow row cultivation is expected to increase soybean yield and save labor for inter-tillage and ridging. Field experiments were performed in 2014 and 2015 to test the effect of plant density (high, middle, and low) under early planting condition on growth, yield, and several agronomical traits of Sachiyutaka A1 and three new genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Models were fitted using hierarchical Bayesian models. conducted under varied environments in the United States (Ball et al, 2000;Heatherly and Elmore, 2004;Lee et al, 2008, De Bruin and Pedersen, 2009, Epler and Staggenborg, 2008Walker et al, 2010;Gaspar and Conley, 2015), Brazil (de Luca et al, 2014), and Japan (Agudamu and Shiraiwa, 2016;Matsuo et al, 2018) also reported different values of AOPDs that were within the range of AOPDs observed in the current study, ranging from 238,000 to 313,000 plants ha -1 . A recent study hypothesized that low plant establishment and survival in a LYE could be one of the potential factors affecting the differential yield response to seeding rate between YEs (Corassa et al, 2018).…”
Section: Yield Componentssupporting
confidence: 76%
“…Models were fitted using hierarchical Bayesian models. conducted under varied environments in the United States (Ball et al, 2000;Heatherly and Elmore, 2004;Lee et al, 2008, De Bruin and Pedersen, 2009, Epler and Staggenborg, 2008Walker et al, 2010;Gaspar and Conley, 2015), Brazil (de Luca et al, 2014), and Japan (Agudamu and Shiraiwa, 2016;Matsuo et al, 2018) also reported different values of AOPDs that were within the range of AOPDs observed in the current study, ranging from 238,000 to 313,000 plants ha -1 . A recent study hypothesized that low plant establishment and survival in a LYE could be one of the potential factors affecting the differential yield response to seeding rate between YEs (Corassa et al, 2018).…”
Section: Yield Componentssupporting
confidence: 76%
“…Selecting the appropriate plant density is an important crop management decision in commercial edamame production where plant architecture determines efficiency of mechanical harvest (Zandonadi et al, 2010). Studies on grain-type soybean report that plant density influences plant height (Matsuo et al, 2018;Mehmet, 2008), number of main stem branches (Agudamu and Shiraiwa, 2016;Board and Kahlon, 2013), and plant biomass (Matsuo et al, 2018). Companies selling edamame seed identify seeding rates ranging from 197,600 plants/ha (Wannamaker Seeds, Saluda, NC) to 344,200 plants/ha (Johnny's Selected Seeds, Winslow, ME), which is similar to recommendations for grain-type soybean (Nafziger, 2009).…”
mentioning
confidence: 54%
“…As shown in Seadh and Abido (2013), Hassan (2015), Asmaa et al (2017), Gulluoglu et al (2016 and, Andres et al (2018) and Matsuo et al (2018).…”
Section: -Effect Of Plant Spacing and Weed Control Treatments On Weedsmentioning
confidence: 96%
“…This includes management of soybean plant spacing and densities, which is one of the important agronomic practices influencing crop growth and productivity (Caliskan et al, 2007;El-Far et al, 2016;Asmaa et al, 2017;Gulluoglu et al, 2017 andMatsuo et al, 2018). Plant density plays an important role in the competitive balance between weeds and soybean.…”
Section: Introductionmentioning
confidence: 99%